HUBUNGAN TINGKAT PENGETAHUAN TENTANG HIV AIDS DENGAN PERILAKU SEKSUAL PRANIKAH PADA NELAYAN DI TPI UNIT II JUWANA PATI JAWA TENGAH - Siti Mas'udah; Sri Setyowati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Introduction: The case of HIV AIDS every year has increased. This is supported by the development of globalization resulting in social changes and lifestyles, including risky behaviors such as sexual intercourse with multiple partners, premarital sex, and drug abuse. Such lifestyle endangers reproductive health, especially the possibility of transmission of sexually transmitted diseases including HIV (Human Immunodeficiency Virus) AIDS (Acquired Immuno Deficiency Syndrome) in couples. Objective: To know the relation of knowledge level about HIV AIDS with premarital sexual behavior to fishermen in TPI Unit II Juwana Pati Central Java.Method: The type of quantitative research design used is descriptive correlasional.Populasi Penelitian Population in this research is the fisherman in TPI Unit II as many as 251 fishermen. The sample of research using non-probability sampling technique that is accidental sampling, as many as 72 respondents, with error rate 10% of the total population. This research was conducted at TPI Unit II of Juwana Central Java. Data were collected using a knowledge-level questionnaire on HIV AIDS and pre-marital sexual behavior. To test hypotasis using test analysis using Kendall Tau.Results: Based on Kendall's Tau correlation test results showed a relationship between HIV AIDS knowledge level and premarital sexual behavior on fishermen in TPI Unit II Juwana Pati Central Java because it has a coefficient of 0.452 with a significance value of 0.000. This shows that p 0,1.Conclusion: There is a significant relationship between HIV AIDS knowledge level and premarital sexual behavior of fishermen in TPI Unit II Juwana Pati Central Java